An optimized protocol for detecting guard cell specific gene expression by in situ RT-PCR in Brassica rapa - Yingying Song; Xinlei Guo; Jian Wu; Jianli Liang; Runmao Lin; Zifu Yan; Xiaowu Wang (Horticultural Plant Journal, 2022)
It is important to detect specific genes expressed in the guard cells, which control gas exchange and play key roles in response to drought and salt stresses. Due to the genetic transformation of Chinese cabbage (Brassica rapa) has not been well developed, in situ RT-PCR is a valuable option for detecting guard cell specific genes. We reported an optimized protocol of in situ RT-PCR by using an FAMA homologous gene Bra001929 in Brassica rapa. FAMA in Arabidopsis has been verified to be specially expressed in guard cells. We designed specific RT-PCR primers and optimized the protocol in terms of the (a) reverse transcription time, (b) blocking time, (c) antigen-antibody incubation time, and (d) washing temperature. Our approach provides a sensitive and effective in situ RT-PCR method for locating expression in the guard cells in Brassica rapa. Moreover, we proved the guard cell specific expression of Bra001929 in the epidermis indicating its’ applicability as a marker gene for guard cells of Brassica rapa.